Buckling Analysis of Stiffened Panels Under Fuselage Bending - Rajan.R.R, Neela; Prince Raja.D, Bino; G, Ramanan.; Sherin.S, Muthu (International Journal of Engineering and Technology, 2018)
The utmost important characteristics in aircraft design were the structure load and safety. One of the main part of an aircraft is Fuselage. Depending on mass scattering of fuselage, the inertia forces will change along the length of the fuselage. Fuselage tends to bend down about axis wing due to Inertia force scattering. This bend will generate tension in upper part of fuselage simultaneously fuselage bottom part will experience compression. This work reveals the issue of the compression buckling of stiffened panels in the bottom portion of the fuselage. A linear static analysis will be carried out on a part of fuselage structure with scattered inertia load. The panels with extreme compression load is recognized for buckling analysis. From static analysis, compression load acting on each panel can be extracted and buckling factor is discovered. MSC PATRAN and MSC NASTRAN are used for this study. From the value of Buckling Factor for both Global and Local analysis of fuselage with different cross-sections, it is clear that the design of the fuselage stiffened panel with â€˜Lâ€™ and â€˜Zâ€™ cross-section is safe one.Â Â